Human monoclonal antibodies targeting α-Gal restrict IgE engagement of α-Gal syndrome allergens - Hyeseon Cho; Youngsil Seo; Haewon Sohn; Shailesh K. Choudhary; Jeff Skinner; Ming Zhao; Ludmila Krymskaya; Weizhi Zhong; Justin Lack; Shanping Li; Boubacar Traore; Joshua Tan; et al. (Journal of Clinical Investigation, 2026)
Allergen-specific monoclonal antibodies (mAbs) that block IgE binding to allergens are emerging as new therapeutics for treating allergies to pollen, peanuts, and cats. Alpha-Gal syndrome (AGS) is an allergy to galactose-α-1,3-Galactose (α-Gal), which is present in mammalian meat and tissue-derived products. Initially aiming to identify mAbs targeting α-Gal on malaria parasites, we isolated 42 α-Gal–specific mAbs from B cells of individuals who had been exposed to malaria but found that they bound weakly to the Plasmodium falciparum parasite. These mAbs predominantly used the IGHV3 gene family and had a wide range of mutation frequencies. We then screened these mAbs for their ability to bind α-Gal on AGS allergens and to block the binding of serum IgE of patients with AGS to AGS allergens. Thirteen mAbs bound to the AGS allergens angiotensin-I-converting enzyme (ACE), aminopeptidase-N (AP-N), and cetuximab, and 2 mAbs— AG028 as both IgA 2 and IgM, and AG050 IgA 1 — blocked the binding of serum IgE from patients with AGS to ACE and AP-N. Additionally, AG028 IgA 2 and AG028 IgM suppressed ACE-mediated activation of basophils sensitized with serum of patients with AGS. This study supports the development of α-Gal–specific mAbs as a new intervention to prevent α-Gal allergy.